The factorial survey as an approach to investigate clinical decision-making: examining influences on a clinician's decision to initiate life-sustaining clinical technology for a child with spinal muscular atrophy type 1 - Quirke, Mary Brigid; Cassidy, Lorna; Alexander, Denise; Walsh, Cathal; Hill, Katie; Masterson, Kate; Flynn, Nia; Brenner, Maria (Frontiers in Pediatrics, 2023)
Background: Spinal Muscular Atrophy (SMA) type 1 is a debilitating condition with a poor prognosis, though therapeutic advances are promising. Long-term ventilation is a common management strategy as respiratory function deteriorates. Without consensus on best practise respiratory management, the decision to initiate invasive LTV (I-LTV) for this group of young children involves many ethical considerations. Understanding the main influencing factors on a clinician's likelihood to initiative I-LTV for a child with chronic critical illness is important to maintain transparency and trust with the family during this challenging time.A factorial survey was used to identify the factors that influence a clinician to support initiation of I-LTV for children with SMA type 1. Factorial survey content was based on literature and evidence-based practice and the content was subject to extensive pretesting and pilot testing. An anonymous survey was disseminated (Oct 2021-Jan 2022), via eight international professional organisations, to clinicians with experience caring for children at the time of initiation of I-LTV.Results: 251 participants answered 514 vignettes on SMA type 1. The greatest influencing factor on clinician's likelihood to initiate I-LTV was parental agreement with the need to initiate I-LTV. Additional qualitative comments from participants support this finding. Clinicians also highlighted the important role of innovative therapies as well as the availability of supports for families when considering initiation however these findings were context based.The factorial survey approach provides a valuable way of identifying influencers on decision-making in sensitive situations. The findings demonstrate the acceptance of the centrality of parental influence in decisions on care delivery. Effective communication with the child's family is key to ensuring shared understanding and agreement of goals of care. More international research is needed on the long-term effects of novel treatments, as well as impact on quality of life and influence of geographical location, to inform decision-making.